Air Navigation Sovereignty Through Indonesia-Singapore Fir Boundary Realignment In 2022 - Jasmine, Divania; Sugara, Robi (Ilomata International Journal of Social Science, 2024)
This research examines the Flight Information Region (FIR) boundary adjustment between Indonesia and Singapore that affects Indonesia's air navigation sovereignty. Various efforts have been made by Indonesia to take over control of the FIR from Singapore, until finally reaching an agreement in adjusting the FIR boundary in 2022. However, in taking over the FIR, Indonesia faced problems, namely the difficulty of Indonesia taking over the management of the FIR which was previously managed by Singapore, as well as challenges in meeting international standards in FIR management. Although the agreement in adjusting the FIR boundary has been agreed, until now the effort has not achieved the expected results in realizing air navigation sovereignty in Indonesia. The purpose of this study is to evaluate how FIR boundary adjustment can improve Indonesia's air traffic management, national security and economic growth. Obstacles include sovereignty issues, international air traffic management standards, and diplomacy between countries. This research uses the policy analysis method by collecting primary and secondary data to analyze the agreement reached in 2022. The results of this study show that the 2022 Indonesia-Singapore FIR adjustment agreement has not fully guaranteed Indonesia's air navigation sovereignty, but this agreement provides significant progress in Indonesian territory. The implications of the results of this study include improving air traffic efficiency and strengthening Indonesia's sovereignty over its airspace, which can also provide insights for future foreign policy and international cooperation.